2016
DOI: 10.1038/srep27895
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signalling in the nucleus accumbens shell is critical for augmented effect of TFF3 on behavioural response to cocaine

Abstract: Neuropeptides play important roles in modulating the rewarding value of abused drugs. Trefoil factor 3 (TFF3) was recently reported to modulate withdrawal syndrome of morphine, but the effects of TFF3 on the cocaine-induced behavioral changes are still elusive. In the present study, cocaine-induced hyperlocomotion and conditioned place preference (CPP) rat paradigms were provided to investigate the role of TFF3 in the reward response to cocaine. High-performance liquid chromatography (HPLC) analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
6
1
Order By: Relevance
“…TOR, specifically mTORC1, is the negative regulator of autophagy. It has been reported that acute cocaine exposure activates the mTOR in cerebral cortex as well as in VTA and NAc . However, we failed to find any changes in the mTOR signaling at 15, 30 or 60 min after a single cocaine exposure in the NAc in vivo or in vitro .…”
Section: Discussioncontrasting
confidence: 87%
“…TOR, specifically mTORC1, is the negative regulator of autophagy. It has been reported that acute cocaine exposure activates the mTOR in cerebral cortex as well as in VTA and NAc . However, we failed to find any changes in the mTOR signaling at 15, 30 or 60 min after a single cocaine exposure in the NAc in vivo or in vitro .…”
Section: Discussioncontrasting
confidence: 87%
“…Several previous studies have demonstrated roles for mTOR signaling in regulating drug-or alcohol-associated behaviors. Trefoil factor 3 (TFF3), a brain-synthesized peptide thought to activate mTOR signaling, can enhance cocaine-induced mTOR activation, hyperlocomotion, and CPP (Luo et al, 2016). Inhibition of GSK-3, an mTORC1 inhibitor, disrupts the reconsolidation of cocaine-associated reward memories (Shi et al, 2014).…”
Section: Effects Of Mtor Deletion On Cocaine-induced Cpp and Synapticmentioning
confidence: 99%
“…Many of the neuropsychiatric, schizophrenia-like side effects of cannabinoids are linked to THC-induced modulation of dopamine (DA) and its downstream signalling pathways, including Akt, GSK-3, mTOR and β-catenin (Renard et al, 2017a,b). These pathways are critical for striatalmediated cognitive and affective processing (Bergeron et al, 2014;Cuesta et al, 2017;Ding et al, 2013;Luo et al, 2016;Xu et al, 2015) and are strongly modulated by THC exposure (Renard et al, 2017a,b). In the mesolimbic pathway, THC is known to modulate DA release dynamics through its actions on CB1 receptors both via pre-synaptic mechanisms and through post-synaptic heteromeric complexes of CB1 and DA receptors (Garcia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%